Politik Hukum Disabilitas: Studi Kasus Perda No. 8 Tahun 2013 di Wonogiri - Muhammad Julijanto (PLD UIN Sunan Kalijaga, 2019)
This study answers the question of how the politics of protection and fulfilment of the rights of persons with disabilities in the case of Regional Disability Regulations in Wonogiri Regency. With a mixed-method between normative legal research and empirical law, the research found that: 1) Regional Regulation No. 8 of 2013 concerning Disability and Empowerment of the Disabled in Wonogiri shows concern and attention to the fulfilment of disability rights along with social security; 2) The politics of disability law is the response of all factions in the DPRD who approve and support the fulfilment of the rights of persons with disabilities through accommodation in regional regulations; 3) Regional Regulations have been implemented largely in stages. Such as the implementation of inclusive education, health services, disability political participation, accessibility for people with disabilities in public facilities and infrastructure.[Penelitian ini menjawab pertanyaan bagaimana politik perlindungan dan pemenuhan hak penyandang disabilitas dalam kasus Peraturan Daerah Disabilitas di Kabupaten Wonogiri. Dengan metode campuran antara penelitian hukum normatif dan hukum empiris, penelitian menemukan bahwa: 1) Peraturan Daerah No. 8 Tahun 2013 tentang Kesetaraan dan Pemberdayaan Difabel di Wonogiri menunjukkan kepedulian dan perhatian terhadap pemenuhan hak-hak disabilitas beserta jaminan sosialnya; 2) Politik hukum disabilitas merupakan respon semua fraksi di DPRD yang menyetujui serta mendukung terpenuhinya hak-hak difabel melalui akomodasi peraturan daerah; 3) Peraturan Daerah ini telah diimplementasikan sebagian besar secara bertahap. Seperti implementasi pendidikan inklusif, pelayanan kesehatan, partisipasi politik difabel, aksesbilitas bagi difabel dalam sarana dan prasarana publik.]